2021
DOI: 10.3390/ijms222010996
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus: A New Therapeutic Candidate for Glioblastoma Treatment

Abstract: Glioblastoma (GBM) is the most aggressive among the neurological tumors. At present, no chemotherapy or radiotherapy regimen is associated with a positive long-term outcome. In the majority of cases, the tumor recurs within 32–36 weeks of initial treatment. The recent discovery that Zika virus (ZIKV) has an oncolytic action against GBM has brought hope for the development of new therapeutic approaches. ZIKV is an arbovirus of the Flaviviridae family, and its infection during development has been associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 117 publications
(170 reference statements)
0
19
0
1
Order By: Relevance
“…ZIKV seems preferentially harmful to the neurons of fetuses and children 35 but seldomly adults, so pathogenic ZIKV infection could be a potential oncolytic therapy against adult GBM. 36 , 37 However, a safe and aspirational viral therapy requires investigation of the mechanism of how, beyond the phenotypic observations, the virus causes specific cell death. Here, we showed that ZIKV could be an oncolytic virus by killing human GBM via viral protease-mediated GSDMD activation.…”
Section: Discussionmentioning
confidence: 99%
“…ZIKV seems preferentially harmful to the neurons of fetuses and children 35 but seldomly adults, so pathogenic ZIKV infection could be a potential oncolytic therapy against adult GBM. 36 , 37 However, a safe and aspirational viral therapy requires investigation of the mechanism of how, beyond the phenotypic observations, the virus causes specific cell death. Here, we showed that ZIKV could be an oncolytic virus by killing human GBM via viral protease-mediated GSDMD activation.…”
Section: Discussionmentioning
confidence: 99%
“…miR-34c can be used to treat GBM or other types of cancer. This particular miRNA can be successfully transmitted by viral vectors or extracellular vesicles [ 129 ].…”
Section: Tumor Suppressor Mirnasmentioning
confidence: 99%
“…As CICs have been shown to be resistant to conventional anticancer therapies, the potential of oncolytic viruses to destroy CICs have made them attractive for alternative therapeutic applications. Oncolytic viruses of different origin [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ] comprise wild-type viruses, which are unable to infect normal cells but are cytotoxic to cancer cells [ 17 ]. Moreover, the deletion of viral genes critical for replication in normal cells but dispensable in cancer cells has generated attenuated oncolytic strains.…”
Section: Characterization Of Oncolytic Self-replicating Rna Virusesmentioning
confidence: 99%
“…Additionally, Aura virus (AURAV) has shown oncotropism for certain tumor cell lines [ 27 ]. In the context of flaviviruses, the Zika virus (ZIKV) has demonstrated oncolytic activity against glioblastoma stem cells (GSCs) [ 14 , 28 ]. The negative-stranded measles viruses (MV) have also demonstrated oncolytic activity in several preclinical studies [ 15 ].…”
Section: Characterization Of Oncolytic Self-replicating Rna Virusesmentioning
confidence: 99%
See 1 more Smart Citation